2014
DOI: 10.1108/josm-01-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of customer feedback on the well-being of service entities

Abstract: IntroductionMarketing in general and services in particular have been blamed for damaging, disregarding, and maltreating consumer's well-being in a multitude of ways; either by having a patronizing style of service delivery, or by underserving groups in needs (Fisk, 2009). As a result, the Transformative Service Research (TSR) movement began. Emerging at the intersection of transformative consumer research and service research (Anderson et al., 2013), TSR is defined as "service research that centers on creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 69 publications
1
45
0
6
Order By: Relevance
“…In this regards, Baron and Warnaby (2011) found that soliciting positive feedback produces valuable information for improving services. Furthermore, personal PCF contributes to the creation of more productive and happier FLEs (Nasr et al, 2014). Similarly, customer empathy was found to act as a qualifier of social interaction by nurturing alignment of feelings and thoughts and creating smooth and harmonious interactions (Gremler and Gwinner, 2008).…”
Section: Positive Customer Feedbackmentioning
confidence: 99%
“…In this regards, Baron and Warnaby (2011) found that soliciting positive feedback produces valuable information for improving services. Furthermore, personal PCF contributes to the creation of more productive and happier FLEs (Nasr et al, 2014). Similarly, customer empathy was found to act as a qualifier of social interaction by nurturing alignment of feelings and thoughts and creating smooth and harmonious interactions (Gremler and Gwinner, 2008).…”
Section: Positive Customer Feedbackmentioning
confidence: 99%
“…Customer feedback can be positive or negative: positive feedback shows firms their strengths as perceived by customers, whereas negative feedback (mostly complaints) is a source to identify problem areas that should be improved (Wirtz, Tambyah, & Mattila, 2010). Customers with higher relationship intentions engage in positive feedback (Nasr, Burton, Gruber, & Kitshoff, 2014) and risk the possible adverse consequences of negative feedback (Lovelock, Wirtz, & Chew, 2009) to display customer citizenship behavior (Liu & Matilla, 2015). Customers with high relationship intentions are subsequently more prone to provide feedback than customers with low relationship intentions (Kumar et al, 2003).…”
Section: Relationship Intentionmentioning
confidence: 99%
“…Moreover, a number of studies show that employee outcomes are correlated with customer outcomes in the service sector (Yoon and Suh, 2003). Therefore, it is not surprising that most of the customer feedback received by service companies has FLEs as the main subjects and recipients (Lovelock and Wirtz, 2010;Nasr et al, 2014).…”
Section: Importance Of Front-line Employeesmentioning
confidence: 99%
“…Thus, TSR calls for studies that uncover and analyze the aspects of the service encounter that have the potential to affect the well-being of FLEs. Nasr et al (2014), drawing on positive psychology and positive organizational behavior theory, identified Positive Customer Feedback (PCF), exchanged during a service encounter, as having a transformational potential and a positive impact on the well-being of FLEs. However, Wood et al (2010) reviewing positive feedback and well-being, noted that: "no research has examined whether there might be a negative side associated with gratitude" (p. 13).…”
mentioning
confidence: 99%